2004
DOI: 10.1080/00015550310006211
|View full text |Cite
|
Sign up to set email alerts
|

Eccrine Porocarcinoma with Bowenoid Changes: Epithelial Membrane Antigen is Not a Useful Marker for Malignant Tumours Arising from Eccrine Gland Structures

Abstract: A case of eccrine porocarcinoma with Bowenoid changes is reported. We compared the results of immunohistochemical staining for epithelial membrane antigen in the present case with results in Bowen's disease to determine whether the presence of epithelial membrane antigen (EMA) enabled us to differentiate between Bowen's disease and eccrine porocarcinoma with Bowenoid changes. Histologically, the present tumour was characterized by atypical clear cells with Bowenoid changes as well as uniform small cells and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…2f). Eccrine porocarcinoma is characterized by epidermotropism and pagetoid diffusion in the epidermis, and may show bowenoid changes 4 . However, in this patient, the BD and eccrine porocarcinoma lesions were separated completely by the SK lesion with sufficient distance to allow each lesion to be clearly identified.…”
Section: Reportmentioning
confidence: 65%
“…2f). Eccrine porocarcinoma is characterized by epidermotropism and pagetoid diffusion in the epidermis, and may show bowenoid changes 4 . However, in this patient, the BD and eccrine porocarcinoma lesions were separated completely by the SK lesion with sufficient distance to allow each lesion to be clearly identified.…”
Section: Reportmentioning
confidence: 65%
“…3,5 Although immunohistochemical detection of carcinoembryonic antigen (CEA) and epithelial membrane antigen (EMA) to highlight the ductal structures support the diagnosis of porocarcinoma, their diagnostic performance has not been evaluated for molecularly confirmed cases. 3,6 In 2019, Sekine et al reported in eccrine poroma and porocarcinoma the detection of recurrent rearrangements of YAP1, a gene encoding for a downstream effector of the Hippo pathway, either with MAML2 or NUTM1. 7 Furthermore, the authors demonstrated that fusion of YAP1 resulted in the loss of expression of the C-terminal part of the YAP1 protein (C-ter YAP1), a phenomenon that can be detected by immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between porocarcinoma and poorly differentiated squamous cell carcinoma (SCC) on morphological and immunohistochemical grounds can be challenging in current practice and based on reported criteria 3,5 . Although immunohistochemical detection of carcinoembryonic antigen (CEA) and epithelial membrane antigen (EMA) to highlight the ductal structures support the diagnosis of porocarcinoma, their diagnostic performance has not been evaluated for molecularly confirmed cases 3,6 …”
Section: Introductionmentioning
confidence: 99%